Nexus of translating contexts: a scoping review on translation studies - Yasin, Nooni Ezdiani; Sukur, Anis Shahirah Abdul (Intelektual Pustaka Media Utama, 2026)
This article conducts a scoping review to illuminate the complex interplay between theory, issues, and effect in translation studies. It aims to map the existing research landscape at the intersection of the three vital components. Highlighting a gap in existing literature, it emphasizes the need for a comprehensive understanding of how these diverse contexts influence translation practices and theoretical frameworks. Employing scoping analysis techniques, the study methodically shifts through relevant literature to identify, select, and synthesize studies that reveal trends, gaps, and emergent themes concerning the contexts on translation. This study uses scoping analysis technique in the Scopus database for the inclusive criteria of 2023 publication year of research article in relation to translation, editing, theory, issues and effect related to translation studies. The findings elucidate that translation studies as a critical intersection of linguistic, cultural, technological, and societal considerations, emphasizing the importance of continuous learning, adaptation, and dialogue among translators, editors, researchers, and practitioners. The conclusion advocates for future research to develop context-aware theoretical and practical approaches, aiming to enhance the effectiveness and cultural relevance of translations. This review sets a foundation for exploring new research directions that could enrich our understanding of the nexus of translation studies.